Impact of Overtraining on Cognitive Function in Endurance Athletes: A Systematic Review - Isabella K. Symons; Lyndell Bruce; Luana C. Main (SpringerOpen, 2023)
Abstract Background Endurance sports require significant training loads to elicit the desired training effects on an athlete's body. However, if adequate recovery is not provided, overtraining may occur, with corresponding decrements in performance. As such, there is a need for measures that can be tracked, to monitor athlete adaptation to training loads, and provide early warning of possible maladaptation. The aim of this review was to determine if a relationship exists between overtraining and cognitive function in endurance athletes. Methods A systematic search of AMED, MEDLINE, SPORTDiscus and APA PsycINFO was conducted. Eligibility criteria included original peer reviewed research, written in English, published between January 2000 and May 2022, and using human participants. Of the 221 articles screened, a total of seven studies met the inclusion criteria and were included in this review. Results The findings of the review suggest that there is a relationship between overtraining and cognitive function with all seven studies finding that cognitive performance declined in response to athletes becoming overreached or overtrained. These studies found that reaction time (as measured by Stroop colour test) increased in response to both overreaching and overtraining. Conclusions Cognitive function tests such as the Stroop Colour Test could be included as part of a broader programme for monitoring athlete adaptation to training.